2007
DOI: 10.1080/14622200701484987
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, but not smokers: Identity among college students who smoke cigarettes

Abstract: Cigarette smoking in college is often described as social smoking, but the term lacks definition and implicitly discounts dependence. We report on college students' use of the terms social smoker and smoker. Students who currently smoked cigarettes were asked whether they considered themselves smokers, and whether they smoked because they were social smokers. The survey was conducted during 1999-2004 at eight colleges; analysis was limited to 1,401 students aged 18-24 years. More than half of students (56.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
146
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 27 publications
11
146
3
2
Order By: Relevance
“…none or different time recall limits in the question; lack of clarity as to whether the reported prevalence levels represent daily, occasional or ever smoking) would need to be addressed in future research in order to facilitate comparisons. An additional point to note is that self-reported smoking rates may underestimate actual current smoking: evidence suggested that numerous young adult college smokers do not classify themselves as 'smokers' (Levinson et al, 2007), given their high prevalence of intermittent (e.g., nondaily) smoking (Grimshaw and Stanton, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…none or different time recall limits in the question; lack of clarity as to whether the reported prevalence levels represent daily, occasional or ever smoking) would need to be addressed in future research in order to facilitate comparisons. An additional point to note is that self-reported smoking rates may underestimate actual current smoking: evidence suggested that numerous young adult college smokers do not classify themselves as 'smokers' (Levinson et al, 2007), given their high prevalence of intermittent (e.g., nondaily) smoking (Grimshaw and Stanton, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, pharmacotherapy or nicotine replacement therapies, appropriate for daily smokers, may be ineffective with other groups of smokers. In addition, college students who are nondaily smokers do not typically consider themselves to be smokers and may underestimate their risk for future smoking, overestimate their ability to quit, and underestimate the health risks associated with their tobacco use ( Levinson et al, 2007 ;Thompson et al, 2007 ). Traditional cessation programs may not be successful with nondaily smokers, primarily because they do not perceive themselves to be smokers.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some light and intermittent smokers do not even consider their use to qualify them as "smokers," demonstrating an unduly optimistic bias in their assessment of smoking's associated risks. [9][10][11]14 Also possible are potentially significant misconceptions regarding the safety of light and intermittent smoking. No level of tobacco exposure is safe.…”
mentioning
confidence: 99%
“…1 Existing data on light and intermittent smoking suggest a potentially alarming picture. Light and intermittent smokers may perceive their tobacco use to be less addictive, [9][10][11] although nicotine dependence symptoms appear to form rapidly in intermittent smokers 12 and the relationship between consumption and addiction does not follow a clear-cut threshold effect. 13 Some light and intermittent smokers do not even consider their use to qualify them as "smokers," demonstrating an unduly optimistic bias in their assessment of smoking's associated risks.…”
mentioning
confidence: 99%